Toward environmental conservation in estudents men and women from Cañete - Gutiérrez Jiménez, Cindy Fiorella (2020)
This study compares school students’ attitudes towards environmental conservation, according to their gender and geographical location: urban and rural school from UGEL 08 in the province of Cañete. In this study, 743 secondary school students were administered the Attitudes towards Environmental Conservation Scale (Yarlequé, 2004), which was adapted for this purpose, demonstrating the validity and reliability of this test. The design of the study is descriptive and comparative. Results: There is a difference in the cognitive dimension between urban and rural students, favoring the latter, and a greater commitment among the female rural students, whose personal qualities are more favorable to environmental conservation.